OPTIMIZATION OF SUB-DISTRICT MANAGEMENT IN ORDER TO IMPROVE PUBLIC SERVICES: OPTIMALISASI MANAJEMEN KECAMATAN DALAM RANGKA PENINGKATAN PELAYANAN PUBLIK - Asbur Hidayat (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2022)
The purpose of this study is to get an idea of the optimization of sub-district management in improving public services to the community. This research uses qualitative research methods using literature studies, namely researchers study diligently the necessary literature. The results showed that in realizing good governance. So the optimization of sub-district management is a must in an effort to improve services by carrying out various government activities include structural, functional and cultural changes. The sub-district is the forefront that is the link between Regent/Mayor and Village, so the Regent /Mayor needs to delegate some government authority to sub-district head. Delegation of authority is not only to provide legalization, but is directed at efforts to increase the effectiveness and efficiency of services to the community appropriately in accordance with the goals that have been set and in accordance with the situation of conditions both for a short period of time and a period of time in the future.